Investigation of the Ducted-Propeller Effects on Aeroacoustic Performance using Phase-Locked PIV - Sun, J.; Yonezawa, K.; Liu, H. (My University, 2023)
This paper presents an integrated study of the aerodynamic and acoustic performance of a shrouded/ducted propeller, with a specific focus on unveiling the underlying mechanisms associated with the aeroacoustic interplay between the duct and propeller. Using phase-locked particle image velocimetry (PIV), we examined three cases: ducted propellers at relative distances of d = 0.11r, d = 0.29r, and a non-ducted propeller. The integrated analysis combining PIV measurements and numerical simulations unveils noise variation mecha-nisms. Our findings demonstrate that a shift in the duct-propeller relative position from d = 0.29r to d = 0.11r can reduce overall sound pressure levels by an average of 5.5 dB. The attenuation in noise is attributed to the maintained integrity of tip vortices and increased diffusion of trailing edge vortex sheets at d = 0.11r. The duct's inlet lip preserves tip vortices, thereby decreasing pressure fluctuations and limiting trailing edge noise.
Keywords: Acoustics